The fallacy of the globalization trilemma: Reframing the political economy of globalization and implications for democracy - Thomas I. Palley (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2017)
This paper argues Rodrik's (2011) globalization trilemma is analytically mistaken. Rather than a trilemma, globalization poses a dilemma between more globalization and reduced national policy space. Not only may globalization shrink policy space, it may also twist it. The character of the twist depends on the type of globalization. There is no inherent contradiction between globalization and the democratic nation state. However, globalization has significant implications for the content of democratic politics which it tends to restrict. Furthermore, globalization can generate policy lock-in (Palley, 2017) which permanently reduces policy space. That has enormous implications for democracy and future democratic policymaking.
Keywords: F0; F02; F50; 330; Globalization; trilemma; dilemma; policy space; policy lock-in; democracy